EFFECT OF ZINGIBEN OFFICINALE PLANT BOILED EXTRACT ON SOME PHYSIOLOGICAL AND BIOCHEMICAL PARAMETEERS IN LOCAL MALE RABBITS - Muntaha Al- Alkatta; Raja Al – Annaz; Iman Al – Sarrag (Mesopotamia Journal of Agriculture)
This study was conducted to investigate the effects of Zingiben Officinale boiled extract on some blood parameters , blood glucose , cholesterol and triglycerides in local male rabbits (6 – 7 months old) . Rabbits were divided into 2 groups (6 rabbits each) . The first group was treated with distilled water (control group) . The second group received the boiled extract of Zingiben Officinale orally at (1000 mg / kg B . wt) daily for 28 days . The results revealed a significant reduction in blood glucose , cholesterol and triglycerides levels and an increase of total leukocytes count and a significant decrease erythrocytes count and hemoglobin concentration.